2017
DOI: 10.4236/ijg.2017.89069
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Structural and Geometrical Parameters of the Kribi-Campo Sedimentary Sub-Basin Using Gravity Data

Abstract: In order to produce a more detailed structural and geometrical information, and determine sediments thickness along the Kribi-Campo sub-basin, statistical spectral analysis and horizontal gradient analysis of residual anomalies coupled with the Euler deconvolution approach were applied on the gravity data in the area. The results obtained from the 2D spectral analysis on anomaly grids gave a depth to the basement rocks of the basin from 0.60 km to 3.93 km. This represents the thickness of the sedimentary forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…The purpose of this study was to provide more information on the nature and the characteristics of the intrusive body in the Lolabe-Campo Area as proposed by [10]. The analysis of the gravity map, the interpretation of the gravity anomalies by spectral analysis, ideal body solution and by 2.5D modelling reveal high gravity discontinuities between rocks of different densities and the presence of two high density bodies of rocks in the subsurface of Lolabe-Campo.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The purpose of this study was to provide more information on the nature and the characteristics of the intrusive body in the Lolabe-Campo Area as proposed by [10]. The analysis of the gravity map, the interpretation of the gravity anomalies by spectral analysis, ideal body solution and by 2.5D modelling reveal high gravity discontinuities between rocks of different densities and the presence of two high density bodies of rocks in the subsurface of Lolabe-Campo.…”
Section: Resultsmentioning
confidence: 97%
“…[8] [9] suggested the presence of high density intrusions in the subsurface of this study area from the analysis and interpretation of the maxima of horizontal gradient of the Bouguer anomalies. In presenting the interpreted structural map of the Kribi-Campo basin, [10] highlighted circular contacts indicating boundaries of intrusions in the Lolabe-Campo zone. In order to provide more detailed information on the nature and the characteristics of this intrusion, after a brief analysis and interpretation of the gravity anomaly map for the study area, this work consists of combining the indirect method (spectral analysis), the inverse method (ideal body solution) and the direct method (2.5D modelling) to analyze and interpret the new gravity data collected in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Where Δg x, y, z# is topographic gravity anomaly value, ρ α, β, h# is the distribution of density contrast in the mass point plane h z#, z is the vertical axis that reflects the distance between topography and the reference Spheroid in a positive direction to the center of the earth, and h is the depth of the equivalent source of point mass measured from the reference Spheroid. The gravity method is used to identify geological sub-surface structures, including gravity anomaly to determine the faults depth and direction of the structures in the sub-surface [7], gravity anomaly to determine the control structure of the plateau [8], gravity to determine uplift and tectonic evolution [9].…”
Section: B Gravitymentioning
confidence: 99%
“…Later, a study [2] has also identified major lineaments in the Kribi-Edea area. Further studies [3] allowed localizing an intrusive body in the northwestern part of Kribi-Campo. An additional study [4] has evaluated the depth of the mafic interface under the transition zone between the southwestern coastal region of Cameroon and the northwestern part of Congo Craton; they showed that an uplift of the mafic interface at depths between 15.6 and 17 km led to a thinning of the crust under the study area.…”
Section: Introductionmentioning
confidence: 99%
“…The gravimetric method is widely used to characterize shallow and deep structures of Cameroon [3,[6][7][8][9]. However, this method could have some limitations depending on whether we use terrestrial or satellite gravity data.…”
Section: Introductionmentioning
confidence: 99%